Application of LFAC {16 2/3Hz} for electrical power transmission system: a comparative simulation study - Salam Waley Shneen; Mahdi Ali Abdul Hussein; Jaafar Ali Kadhum; Salah Mahdi Ali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Transmission of electrical power for long distance is one of the major challenges for electrical engineers over the years. The first and foremost target it is to ensure the transport of electric power with minimal losses over the distance. This paper proposes to employ the low frequency alternating current (LFAC) with (16 2/3Hz) instead of the traditional frequency (50Hz) for electrical power transmission based on a simulation study. Two transmission systems have been constructed using MATLAB/Simulink software namely: 50Hz transmission systems and (16 2/3Hz) transmission systems. In addition, three different distances of transport lines have been used to compare the efficiency of the two systems namely: short (50km), medium (150) and long (300km). The result demonstrated that the use of LFAC with (16 2/3Hz) is better than the traditional frequency (50Hz) in term of energy saving.